INTERACTION IN EFL WRITING CLASS: LECTURERS’ REFLECTION - Monalisa Monalisa (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
ABSTRACT In writing class, producing a well-polished text passes two main stages: pre writing and drafting. During these stages, interactions take place which can be in form of learners-learners and learners-lecturers interactions. Dealing with this, two main questions should be directed towhat practices of interaction conducted during writing class and how lecturers reflect them. The data were collected from four writing lecturers of English Education Program of State Islamic University Sulthan Thaha Saifudin Jambiwho have at least two years teaching experience. An interview conducted to each of them to explore what interactions were facilitating and less facilitating learners.The result showed that oral and written interaction were found from both learners-learners and learners-lecturers interactions.As reflected by the lecturers, both oral and written interactions made sense for the learners with particular assistances. Specifically, a long written comments on the learners’ drafts contributed better revision. ABSTRAK Untuk memproduksi sebuah teks yang terpoles dengan baik, ada dua tahapan utama yang dilalui di kelas Writing yakni tahapan pramenulis dan tahapan membuat draft. Selama tahapan tersebut, interaksi berlangsung antara mahasiswa dengan mahasiswa dan antara dosen dengan mahasiswa. Terkait dengan hal ini, ada dua pertanyaan yang diajukan yakni apa saja praktek interaksi yang terjadi di kelas Writing dan bagaimana dosen merefleksikannya. Data penelitian ini dikumpulkan dari empat orang dosen Writing di program studi pendidikan Bahasa Inggris UIN Sulthan Thaha Saifudddin Jambi yang memiliki pengalaman mengajar paling sedikit dua tahun. Interview dilakukan dengan mereka untuk mengetahui interaksi apa saja yang dapat memfasilitasi mahasiswa dalam menulis. Temuan menunjukkan bahwa terdapat interaksi secara oral dan tertulis dari mahasiswa dengan mahasiswa dan mahasiswa dengan dosen. Seperti yang direfleksikan oleh para dosen, kedua tipe interaksi tersebut bermakna bagi mahasiswa dengan asistensi khusus. Temuan spesifiknya adalah bahwa komentar panjang tertulis pada draft mahasiswa mampu membuat revisi draft mereka menjadi lebih baik.How to Cite: Monalisa. (2017). Interaction in EFL Writing Class: Lecturers’ Reflection. IJEE (Indonesian Journal of English Education), 4(2), 144-155. doi:10.15408/ijee.v4i2.8323